The relationship of consumer psychology and consumer experience to consumer satisfaction and organisational performance: literature review - Petr Suchánek; Simona Činčalová (Cogent Business & Management, 2024)
Consumer psychology, consumer experience, consumer satisfaction, and organizational performance constitute domains that exert a direct or indirect influence on a company's operational efficacy. Despite their inherent expansiveness, these realms are typically scrutinized discretely and frequently devoid of explicit linkage to organizational performance. Nonetheless, their interrelations enable the characterization of consumer profiles and the quantification of these attributes. Should these characteristics manifest in a company's performance, they can be leveraged through various managerial tools. This article endeavors to systematically review literature across these domains via a structured literature inquiry to foster a holistic understanding of the consumer paradigm, particularly emphasizing satisfaction dynamics and influential factors, notably rooted in psychological and experiential frameworks. Such insights are pivotal for enhancing organizational performance. The chosen methodology, a systematic literature review, specifically a structured approach, is deemed optimal for its comprehensive coverage of diverse facets of consumer behavior and their nexus with organizational outcomes. Our inquiry advocates for a mixed-methods research design targeting customers of select companies within a specific national and industrial context. The inquiry encompasses consumer satisfaction, personality (as a constituent of consumer psychology), consumer experience, consumer cognition (as a component of consumer experience), and organizational (financial) performance. Despite the absence of comprehensive research in these areas, this study promises to unearth transformative insights for enhancing organizational efficacy. It is recommended to conduct extensive research with a mixed design, within the selected country and industry, which will be focused on customers of selected companies.
Keywords: 650; consumer satisfaction; consumer psychology; consumer experience; organisational performance